(untitled) (LACCEI, 2024)
The world is constantly changing, awareness about caring for our planet is growing and brings with it changes, among which is the paradigm of the economy. Reducing the economic and environmental cost of the processes must be the challenge. Contamination with metals can cause different harmful effects since they are not degradable and bioaccumulative. Although some metals are essential, in excess all of them can produce harmful effects on the biota and consequently generate the loss of biodiversity with destruction of the ecosystem in the long term. In Argentina, the National Law 24,051 on hazardous waste places limits on the discharge of large amounts of substances, including metallic species such as nickel, chrome, copper, lead, etc. On the other hand, large amounts of natural materials are considered waste that, however, could be reused as pollutant-removing materials, entering a circular economy loop. Thus, water treatment using materials discarded by another industry could be the solution. Residues such as peanut shells (Argentina, with 400,000 tons per year, is the tenth largest producer in the world) or certain aquatic plants considered a pest by the FAO can be used as metal adsorbent materials. Aquatic macrophytes Salvinia molesta, Azolla pinnata, Lemna minor, Limnobium leaveigatum and Pistia stratiotes peanut shell (Arachis hypagaea), trunks, branches and moringa (Moringa oleifera) husks were used as adsorbents in tests for metal removal. These previously treated materials were characterized by the BET isotherm, FTIR studies, impurity release by TXRF, zero charge pH curves and later used for metal removal. For nickel, depending on the working conditions, removal efficiencies greater than 92% will be obtained for Azolla, peanut shells, moringa residues and Salvinia. For Lemna, Limnobium and Pistia stratiotes the % removal was less than 30 %. Subsequently, the dosage curves, the kinetic and adsorption equilibrium studies were carried out with the adjustment of the different models to the experimental data.